Black Preaching in Brown Places: Towards the Development of a Black Mestizo Homiletic (Homiletic, 2015)
Many Black neighborhoods across the United States are becoming increasingly Latin@. Black churches in these neighborhoods will need to adjust their ministry practices in order to build community amongst this changing demographic. Borrowing Elizondo’s notion of mestizo as one who can operate as both insider and outsider in different cultural locations, this paper begins to reimagine Black preaching in the churches that serve these changing neighborhoods. Using the postcolonial themes of marginality, hybridity, and self-reflexivity, this paper proposes the beginnings of a Black Mestizo homiletic that looks to merge Black and Latin@ preaching traditions in order to form congregations representative of the community.